2019
DOI: 10.1128/msphere.00052-19
|View full text |Cite
|
Sign up to set email alerts
|

A Cohort Study of the Impact of Carbapenem-Resistant Enterobacteriaceae Infections on Mortality of Patients Presenting with Sepsis

Abstract: The objective of this study is to evaluate the impact of carbapenem-resistant Enterobacteriaceae (CRE) infection on sepsis 30-day mortality. A retrospective cohort of patients >18 years old with sepsis and organ dysfunction or septic shock was conducted. Univariate analysis was done for variables potentially related to 30-day mortality, and the ones with P values of <0.05 were included in a backward stepwise hierarchic Cox regression model. Variables that remained with P values of <0.05 were retained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 16 publications
1
31
0
6
Order By: Relevance
“…The course of CRE bloodstream infection (BSI) in immunocompromised patients is usually abrupt and fatal [4]. A cohort study of the impact of CRE infections on mortality of patients presenting with sepsis showed that patients with CRE infections had signi cantly higher 30-day mortality: 63.8% versus 33.4% (P < 0.01) [5].…”
Section: Introductionmentioning
confidence: 99%
“…The course of CRE bloodstream infection (BSI) in immunocompromised patients is usually abrupt and fatal [4]. A cohort study of the impact of CRE infections on mortality of patients presenting with sepsis showed that patients with CRE infections had signi cantly higher 30-day mortality: 63.8% versus 33.4% (P < 0.01) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Infection with CRE increases the risk for prolonged hospitalization, with risk of mortality being higher in patients with CRE bacteremia, and correlating directly with the development of septic shock and the use of incorrect empirical antibiotic therapy (6). Moreover, mortality risk associated with CP-CRE infections is 3-6 times higher compared to that of infections caused by a non-resistant bacteria (12).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, antibiotic susceptibility testing (AST), which can only be performed after the growth of the pathogen colonies on solid medium, demands approximately 24 hours. Each delay in pathogen identification and antibiotic treatment adjustment has serious implications for patients, particularly with regards to infections with multidrug resistant bacteria such as carbapenem-resistant Enterobacterales (CRE) (4)(5)(6). Therefore, rapid assays for pathogen identification in BSI are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the assay was demonstrated to perform well for direct detection of CRE bacteria in blood culture, without the need for bacterial cultivation [ 10 ]. Several studies have evaluated the reliability of the NG-Test CARBA 5 kit as a diagnostic tool for recognition of CRE in bacterial colonies [ 10 , 11 ]. The current work assessed the kit’s performance and lower limit of detection in blood CRE samples.…”
Section: Introductionmentioning
confidence: 99%